Soundproofing ability and mechanical properties of polypropylene/exfoliated graphite nanoplatelet/carbon nanotube (PP/xGnP/CNT) composite - Kim, Myung-Sub; Yan, Jun; Kang, Kyung-Min; Joo, Kyung-Hoon; Kang, Yeon-June; Ahn, Sung-Hoon (International journal of precision engineering and manufacturing, 2013)
Exfoliated graphite nanoplatelets (xGnPs) are platelet-like graphite nanocrystals with multi-graphene layers. They are promising materials for use as nanofillers in polymer composites due to their high conductivity, unique graphitized plane structure, and low manufacturing cost. Mixed polypropylene (PP)/xGnPs/carbon nanotube (CNT) composites were fabricated by a solution blending method. The soundproofing characteristics, mechanical properties, and physical morphologies of the composites were investigated at different filler loads with various nanomaterials. The tensile strength of the pure PP is 26.4 MPa. The PP/0.3 wt% xGnPs/0.5 wt% CNT composite had a tensile strength of 34.2 MPa, an increase of 29% relative to that of PP. Compared to PP, the composite material blocked an additional 3 dB of sound at frequencies between 520 Hz and 640 Hz. TEM images of the PP/xGnP/CNT composites showed that the CNTs were homogeneously dispersed and connected to the xGnP sheets in the PP matrix. The xGnP and CNT nanofillers formed 3D hybrid architectures that afforded remarkable improvements in mechanical and soundproofing properties.